2021
DOI: 10.3390/medicina57070669
|View full text |Cite
|
Sign up to set email alerts
|

A 2021 Update on the Use of Liraglutide in the Modern Treatment of ‘Diabesity’: A Narrative Review

Abstract: Obesity and type 2 diabetes mellitus have become a significant public health problem in the past decades. Their prevalence is increasing worldwide each year, greatly impacting the economic and personal aspects, mainly because they frequently coexist, where the term “diabesity” may be used. The drug class of glucagon-like peptide 1 receptor agonists (GLP-1 RAs) is one of the most modern therapy options in managing these metabolic disorders. This review focuses on the effects of liraglutide, a long-acting GLP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
1
20
0
9
Order By: Relevance
“…Moreover, when the drug was combined with physical activity, it significantly increased weight loss compared to liraglutide alone or physical exercise alone. These results reinforce the benefits of liraglutide in weight loss and emphasize the fundamental role of physical activity in chronic weight control ( Lundgren et al, 2021 ; Tilinca et al, 2021 ).…”
Section: Interventions To Reduce the Effects Of Obesitysupporting
confidence: 77%
“…Moreover, when the drug was combined with physical activity, it significantly increased weight loss compared to liraglutide alone or physical exercise alone. These results reinforce the benefits of liraglutide in weight loss and emphasize the fundamental role of physical activity in chronic weight control ( Lundgren et al, 2021 ; Tilinca et al, 2021 ).…”
Section: Interventions To Reduce the Effects Of Obesitysupporting
confidence: 77%
“…Neuronal circuits are activated, and food intake declines as satiety signals like CCK and GLP-1 are created during food ingestion, signaling the conclusion of the meal. Finally, GLP-1 injections into the body over an extended period of time decrease weight gain and promote weight loss [ 23 ]. This is also supported by the observation that obese people have lower GLP-1 levels than lean people [ 24 ].…”
Section: Bodymentioning
confidence: 99%
“…In fact, between 1975 and 2016, the rate of obesity tripled and continuously escalated in pandemic-like proportions. 1 In 2016 alone, data from the World Health Organization (WHO) revealed that more than 1.9 billion adults aged 18 years and above were overweight, 650 million of whom were obese. The prevalence of overweight and obesity is reported to be higher in women than in men across the globe, in both developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%